A data hiding scheme based on the difference of image interpolation algorithms - Bai, Xuemei; Chen, Yong; Duan, Gangpeng; Feng, Chao; Zhang, Wanli (Journal of information security and applications, 2022)
Interpolation is a mature technique used in image processing and many data hiding schemes based on image interpolation have been proposed. In this paper, a novel efficient data hiding scheme based on the difference between image interpolation algorithms is proposed. The interpolated values obtained by neighboring points using different interpolation algorithms are generally different, and the difference can be used for encoding secret data. 2k different interpolated values calculated by 2k different interpolation algorithms respectively in the ideal case, and they are numbered in increasing order to correspond to the k bits secret data in each interpolated pixel. At the receiver's side, the secret data can be obtained based on the matching of the sorting results of these interpolation values of the accepted interpolation values. In fact, different algorithms may produce the same interpolation values, it is necessary to modify the appropriate number of interpolation value so that the number of different interpolation values reaches 2k, then the following image hiding procedures can employ the method of ideal case. The experimental results show that the proposed hiding scheme provides high embedding capacity with good visual quality.